2009
DOI: 10.1159/000226229
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Stimulated C-Reactive Protein Production by Human Coronary Artery Endothelial Cells

Abstract: Background: Obesity and cardiovascular disease are closely related. Leptin, an adipocyte-produced hormone, is associated with increased cardiovascular risk. Increased plasma levels of leptin are measurable in the plasma of obese individuals. However, the possible links between obesity and cardiovascular disease are not completely understood. C-reactive protein (CRP) is a predictor of future cardiovascular events and plays a role in atherothrombotic disease. Thus, we evaluated whether leptin might play a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 70 publications
3
39
0
1
Order By: Relevance
“…Pulmonary vascular production of CRP In agreement with previous findings reporting that vascular SMCs are the major source of CRP local production in systemic injured or atherosclerotic arteries [38] and that vascular ECs may also produce CRP [39], this is the first study to report a local production of CRP by ECs and SMCs in CTEPH proximal pulmonary arterial tissue. This locally produced CRP might contribute to endothelial dysfunction, vascular remodelling and in situ thrombosis in CTEPH ( fig.…”
Section: In Vitro Effects Of Crp On Pulmonary Vascular Cellssupporting
confidence: 90%
“…Pulmonary vascular production of CRP In agreement with previous findings reporting that vascular SMCs are the major source of CRP local production in systemic injured or atherosclerotic arteries [38] and that vascular ECs may also produce CRP [39], this is the first study to report a local production of CRP by ECs and SMCs in CTEPH proximal pulmonary arterial tissue. This locally produced CRP might contribute to endothelial dysfunction, vascular remodelling and in situ thrombosis in CTEPH ( fig.…”
Section: In Vitro Effects Of Crp On Pulmonary Vascular Cellssupporting
confidence: 90%
“…Statin also suppresses leptin expression in adipocytes and human coronary artery endothelial cells [18,19]. The effect of statin on leptin expression in VSMCs is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular damage starts early as Al-Tahami showed that coronary microvascular dysfunction was more prevalent in young obese compared to young lean individuals [14]. Obesity can be associated with elevated CRP concentrations via enhanced leptin secretion and consecutive CRP release from endothelial cells [15]. In addition, Khera et al [16] reported important gender differences regarding body fat pattern resulting in higher CRP levels in obese women compared to men.…”
Section: Discussionmentioning
confidence: 99%